The relationship between sedentary behavior and eating patterns with nutritional status of Makassar Adolescents - Herani Khaerunnisa; Andi Irhamnia Sakinah; Iip Larasati; Risma Irnawati; Arifuddin Ahmad (AcTion: Aceh Nutrition Journal, 2025)
Modern lifestyles that lead to sedentary behavior and unbalanced diets are major health concerns for adolescents. Sedentary behavior and unbalanced diets have a negative impact on nutritional status. This study aimed to identify the relationship between sedentary behavior, diet, and nutritional status in adolescents in Makassar City. This observational, analytical, quantitative, cross-sectional study was conducted on adolescents aged 14-15 years from five schools in Makassar from October to December 2024. A total of 286 respondents were selected using a Proportionate Stratified Random Sampling technique. Data were collected through questionnaires, interviews, and anthropometric measurements and then analyzed using the chi-square test. The results showed a significant relationship between sedentary behavior (p = 0,001) and diet (p = 0,031) with nutritional status. The majority had moderate sedentary behavior, poor diet, and good nutritional status. The study concluded that adolescents have diverse nutritional needs based on both direct and indirect factors